This should be easy because we just have to use substitution method. Substitute the value of x from the second equation into the x of the first equation.
-4(2y) + 11y = 15
-8y + 11y = 15
3y = 15 ; y = 5
Substitute this value of y to either the first or second equation.
x = 2(5) = 10
The ordered pair is therefore (10,5).
Answer:
a is equal to 0.3
Step-by-step explanation:
12a + 5 -8a =-1
(collect like terms)
12a + 8a= -1 -5
20a = -6
a= -6÷20
a= 3÷ 10
a= 0.3
√(25/4) =√(5²/2²) =5/2
Hope it helps you